Dental attitudes: proximal basis for oral health disparities in adults - Riley JL III, Gilbert GH, Heft MW. (Blackwell Synergy, 2006)
Behavioral science postulates that underlying characteristics of populations, rather than sociodemographic groupings, are more proximal causes of oral health disparities through differing oral health behaviors.